Analysis and Correction the Inter-channel Mismatch of Synthetic Aperture Radiometer - Xianxun Yao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A Ka-band two dimensional synthetic aperture interferometric radiometer (SAIR) called SAIR-2D has been developed for concealed weapon detection. The inter-channel mismatch due to amplitude, phase and group delay differences between each receiving channel pairs can result in an undesired effect called fringe washing function (FWF). As the security application usually needs a wide field of view, the FWF is unavoidable and could lead to radiometric performance degradation. This paper presents a general method to analyze the impact of inter-channel mismatch on SAIR. Based on the analysis, the performance degradation of the SAIR-2D is mainly introduced by the group delay difference. To decrease the degradation, a synchronization module is designed to correct the group delay difference. Validation experiments have been conducted on SAIR-2D. The experimental results have validated that the correction technique can meet the requirements of SAIR-2D. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.2890